A sulfonimide derivative of bezafibrate as a dual inhibitor of cyclooxygenase-2 and PPARα - Ammazzalorso, Alessandra; Tacconelli, Stefania; Contursi, Annalisa; Hofling, Ulrika; Cerchia, Carmen; Di Berardino, Sara; De Michele, Alessandra; Amoroso, Rosa; Lavecchia, Antonio; Patrignani, Paola (Frontiers in Pharmacology, 2024)
Background. PPARα and cyclooxygenase (COX)-2 are overexpressed in certain types of cancer. Thus, developing a dual inhibitor that targets both could be more effective as an anticancer agent than single inhibitors. We have previously shown that an analog of the bezafibrate named AA520 is a PPARα antagonist. Herein, we report the identification of AA520 as a potent COX-2 inhibitor using in-silico approaches. In addition, we performed a thorough pharmacological characterization of AA520 towards COX-1 and COX-2 in different in vitro models. Methods. AA520 was characterized for inhibiting platelet COX-1 and monocyte COX-2 activity in human whole blood (HWB) and for effects on lipidomics of eicosanoids using LC-MS/MS. The kinetics of the interaction of AA520 with COX-2 was assessed in the human colon cancer cell line, HCA-7, expressing only COX-2, by testing the COX-2 activity after extensive washing of the cells. The impact of AA520 on cancer cell viability, metabolic activity, and cytotoxicity was tested using the MTT reagent. Results. In HWB, AA520 inhibited in a concentration-dependent fashion LPS-stimulated leukocyte prostaglandin (PG)E2 generation with an IC50 of 0.10 (95% CI: 0.05-0.263) M while platelet COX-1 was not affected up to 300 M. AA520 did not affect LPS-induced monocyte COX-2 expression, and other eicosanoids generated by enzymatic and nonenzymatic pathways. AA520 inhibited COX-2-dependent PGE2 generation in the colon cancer cell line HCA7. Comparison of the inhibition of COX-2 and its reversibility by AA520, indomethacin (a time-dependent inhibitor), acetylsalicylic acid (ASA) (an irreversible inhibitor), and ibuprofen (a reversible inhibitor) showed that the compound is acting by forming a tightly bound COX-2 interaction. This was confirmed by docking and molecular dynamics studies. Moreover, AA520 (1 M) significantly reduced MTT in HCA7 cells. Conclusions. We have identified a highly selective COX-2 inhibitor with a unique scaffold. This inhibitor retains PPARα antagonism at the same concentration range. It has the potential to be effective in treating certain types of cancer, such as hepatocellular carcinoma (HCC) and renal cell carcinoma (RCC), where COX-2 and PPARα are overexpressed.